Alternative U.S. biofuel mandates and global GHG emissions: The role of land use change, crop management and yield growth - Mosnier, Aline; Havlík, Petr; Valin, Hugo; Baker, J.; Murray, B.; Feng, S.; Obersteiner, Michael; McCarl, B.A.; Rose, S.K.; Schneider, U.A. (Elsevier, 2013)
We investigate the impacts of the U.S. renewable fuel standard (RFS2) and several alternative biofuel policy designs on global GHG emissions from land use change and agriculture over the 2010-2030 horizon. Analysis of the scenarios relies on GLOBIOM, a global, multi-sectoral economic model based on a detailed representation of land use. Our results reveal that RFS2 would substantially increase the portion of agricultural land needed for biofuel feedstock production. U.S. exports of most agricultural products would decrease as long as the biofuel target would increase leading to higher land conversion and nitrogen use globally. In fact, higher levels of the mandate mean lower net emissions within the U.S. but when the emissions from the rest of the world are considered, the US biofuel policy results in almost no change on GHG emissions for the RFS2 level and higher global GHG emissions for higher levels of the mandate or higher share of conventional corn-ethanol in the mandate. Finally, we show that if the projected crop productivity would be lower globally, the imbalance between domestic U.S. GHG savings and additional GHG emissions in the rest of the world would increase, thus deteriorating the net global impact of U.S. biofuel policies.